2021
DOI: 10.1097/tp.0000000000003496
|View full text |Cite
|
Sign up to set email alerts
|

Imlifidase Desensitization in Crossmatch-positive, Highly Sensitized Kidney Transplant Recipients: Results of an International Phase 2 Trial (Highdes)

Abstract: Background. Highly HLA sensitized patients have limited access to life-saving kidney transplantation because of a paucity of immunologically suitable donors. Imlifidase is a cysteine protease that cleaves IgG leading to a rapid decrease in antibody level and inhibition of IgG-mediated injury. This study investigates the efficacy and safety of imlifidase in converting a positive crossmatch test to negative, allowing highly sensitized patients to be transplanted with a living or deceased donor kidney. Methods. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 26 publications
0
82
0
2
Order By: Relevance
“…This endopeptidase rapidly cleaves all IgG into F(ab’) and Fc fragments to impair the effector function from all circulating IgG. In both phase 1 and 2 desensitization trials, this agent led to a precipitous drop in DSA within hours, and therefore is a valuable tool for deceased donor positive crossmatch transplantation to avoid hyperacute rejection ( 44 , 52 ). The main limitation is that this drug will likely need to be part of a combination therapy regimen because it only cleaves circulating antibody and antibody levels begin to have a brisk rebound within 3-7 days ( 44 , 52 ).…”
Section: Emerging Therapeutics For Desensitizationmentioning
confidence: 99%
“…This endopeptidase rapidly cleaves all IgG into F(ab’) and Fc fragments to impair the effector function from all circulating IgG. In both phase 1 and 2 desensitization trials, this agent led to a precipitous drop in DSA within hours, and therefore is a valuable tool for deceased donor positive crossmatch transplantation to avoid hyperacute rejection ( 44 , 52 ). The main limitation is that this drug will likely need to be part of a combination therapy regimen because it only cleaves circulating antibody and antibody levels begin to have a brisk rebound within 3-7 days ( 44 , 52 ).…”
Section: Emerging Therapeutics For Desensitizationmentioning
confidence: 99%
“…Among patients completing the original 6 months of posttransplant follow‐up in the Phase 2 studies, renal function was acceptable and relatively stable. Findings on surveillance biopsies were generally favorable, with little evidence of acute or chronic active AMR beyond the early initial period 13 . Although additional protocol biopsies are not available, the eGFR in most patients remains stable up to 3 years.…”
Section: Discussionmentioning
confidence: 92%
“…8,12 Most cases of rebound DSA responded favorably to antibody reduction therapies in the Highdes trial, including plasmapheresis, IVIG, rituximab, and bortezomib. 14 Given the existing experience in kidney transplantation, current and future clinical trials of imlifidase for transplantation will administer it in combination with other therapies to inhibit repopulation of antibodies. Moving forward, the strategy will be to time these therapies in a sequence that optimizes the efficacy of each agent and avoids interactions.…”
Section: K Ine Ti C S Of Antibody Rebound Following Tre Atment With I...mentioning
confidence: 99%
“…Similarly, in the Highdes trial, there were no serious infections reported by the investigators as related to imlifidase and only one non-serious infection that was considered probably related (urinary tract infection). 14 There were seven treatment-emergent adverse events considered possibly or probably related to treatment in the Highdes trial. 14 These included two infusion-related reactions, one of which was considered related to the treatment where the infusion was discontinued.…”
Section: Sa Fe T Ymentioning
confidence: 99%